A Stylistic Analysis of the Linguistic Deviations in Cummings’ “In Just-/Spring” - Wu, Sufen (Lingual Journal of Language and Culture; Vol 16 No 2 (2023): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2023.v16.i02.p02, 2023)
E. E. Cummings, known as a pioneer and a distinguished representative in the area of experimental poetry in the 20th century, enjoys enduring fame and great popularity for the simplicity of his language and the playful mode in his poems. “in Just-/spring” is one representative, in which Cummings experiments radically with form, punctuation, and spelling to create a new, highly idiosyncratic means of poetic expression. By doing so, Cummings makes the thematic significance buried under the surface of the poem. Therefore, this paper, based on literary stylists Geoffrey Leech’s remarks about deviation, aims to analyze lexical deviation and graphological deviation in the poem, hoping to provide a stylistic analysis of the poem and trying to dig out how this maverick poet integrates his cubist strategy into his poem “in Just-/spring” in an attempt to express his eulogy of innocence.